A “clearcut” case? Brown bear selection of coarse woody debris and carpenter ants on clearcuts - Frank, Shane C. (For Ecol Manage, 2015)
Forest management alters habitat characteristics, resulting in various effects among and within species. It is crucial to understand how habitat alteration through forest management (e.g. clearcutting) affects animal populations, particularly with unknown future conditions (e.g. climate change). In Sweden, brown bears (Ursus arctos) forage on carpenter ants (Camponotus herculeanus) during summer, and may select for this food source within clearcuts. To assess carpenter ant occurrence and brown bear selection of carpenter ants, we sampled 6999 coarse woody debris (CWD) items within 1019 plots, of which 902 were within clearcuts (forests ⩽30 years of age) and 117 plots outside clearcuts (forests >30 years of age). We related various CWD and site characteristics to the presence or absence of carpenter ant galleries (nests) and bear foraging sign at three spatial scales: the CWD, plot, and clearcut scale. We tested whether both absolute and relative counts (the latter controlling for the number of CWD items) of galleries and bear sign in plots were higher inside or outside clearcuts. Absolute counts were higher inside than outside clearcuts for galleries (mean counts; inside: 1.8, outside: 0.8). CWD was also higher inside (mean: 6.8) than outside clearcuts (mean: 4.0). However, even after controlling for more CWD inside clearcuts, relative counts were higher inside than outside clearcuts for both galleries (mean counts; inside: 0.3, outside: 0.2) and bear sign (mean counts; inside: 0.03, outside: 0.01). Variables at the CWD scale best explained gallery and bear sign presence than variables at the plot or clearcut level, but bear selection was influenced by clearcut age. CWD circumference was important for both carpenter ant and bear sign presence. CWD hardness was most important for carpenter ant selection. However, the most important predictor for bear sign was the presence or absence of carpenter ant galleries. Bears had a high foraging “success” rate (⩾88%) in foraging CWD where galleries also occurred, which was assessed by summing CWD items with the concurrence of bear sign and galleries, divided by the sum of all CWD with bear sign. Clearcuts appeared to increase the occurrence of a relatively important summer food item, the carpenter ant, on Swedish managed forests for the brown bear. However, the potential benefit of this increase can only be determined from a better understanding of the seasonal and interannual variation of the availability and use of other important brown bear food items, berries (e.g. Vaccinium myrtillus and Empetrum spp.), as well as other primary needs for bears (e.g. secure habitat and denning habitat), within the landscape mosaic of managed forests.